MAKNA KARIKATUR JITET TERKAIT PEMILIHAN PRESIDEN INDONESIA 2014 PADA RUBRIK OPINI DI SURAT KABAR KOMPAS - Sanjaya, Rendra (Istek Widuri Jakarta, 2020)
This research study the meaning contained in the caricature by Jitet Koestana. This caricature is related to the 2014 Presidential Election in the Opinion Rubric of Kompas using a qualitative descriptive method. Descriptive method is used to find and collect data, compose, use and interpret data. The data in this study are in the form of written sources, namely books, archives, and documents, as well as statements of informants obtained from in-depth interviews. In-depth interviews were conducted based on a list of questions that had been prepared. Observations were also made to determine the situation directly in the field. In this case, the researcher made participatory observations by being directly involved in daily activities with the source of the informant. In this study, the authors tested the validity of the data obtained by using the triangulation technique. Triangulation is done by comparing or cross-checking the data obtained, namely the results of observations with interviews and related documents. After conducting the analysis, it is concluded that Jitet Koestana's caricature tries to construct the reality of various problems that arise as a result of the rivalry between the two presidential candidates in the 2014 presidential election. In addition, Kompas, especially Jitet, also tries to be neutral and favor the small people. Alignment to the little people can be seen in the appearance of characters who are characteristic of his caricatures.